Rancang Bangun Egrek Sentak Manual - Putri, Indah Purnama; Febrianton, Adi; Akbar, Rahmad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Palm oil is an industrial/plantation plant that is useful as a producer of cooking oil, industrial oil and fuel. In the world, Indonesia is the largest country that produces palm oil. Most of the harvesters of fresh fruit bunches (FFB) and oil palm fronds still use manual methods with egrek and dodos harvesting tools. Using a manual egrek requires quite a lot of energy and a long time in the harvesting process, therefore a tool is needed that can reduce energy and time but the price is still affordable for oil palm farmers. The egrek pipe is a tool used to cut fronds and fresh fruit bunches. Iron pipe is a mixture of aluminum containing 4% copper. Pipes and pipes can be modified into cutters of fronds and fresh fruit bunches. Modification of the tool utilizes iron pipes, iron plates, iron sticks and pipes. The principle is done by moving the tool that is designed and made forward and backward.